Imperialismo, dependência e globalização: a contemporaneidade capitalista - Cardeal, André Morato Dias (2007)
The contemporanity is marked by transformations in the structure of the world-wide capitalism, for the expansion of the integration of the markets, for transformations in the technique, the existence of an only hegemonic country and amongst other characteristics, also for the destruction of what existed and was called real socialism . It is the exactly context that proliferates, in the most diverse shades of thought, different interpretations of this reality, that is, the world-wide capitalist system. Thus terms like globalization and neoliberalism appear together many others trying to give some form, make possible the interpretation and the knowledge of this reality, in its various aspects. This work, since a marxist theoretical reference, investigates the characteristics of the world-wide economy in the contemporanity, searching, recoup diverse contributions made for authors who have marxist theory as reference, for help in the development of this important shade of interpretation of the reality, and, from this theoretical recovery, help to understand the contemporanity of the capitalist system. In such a way this work opposes the dominant thesis which affirms that the present time would be a new stage in the capitalism, the globalization. Stage that would be marked by a supreme evolution, without precedents, with new characteristics, that would be expressed through the expansion of the opportunities, of the dissolution of the differences, of the nationalities, and the negation of the imperialist stage. Therefore, what can be perceived through the analysis and the raised data, is that in contrast of the panacea promoted by the multilateral institutions, world-wide capitalist economy is marked today by the deepening of the proper capitalism logic, that is not different of that which reigned in the principle of the last century. Of this form, it is pointed that the globalization that would reign today could be understood as the globalization of the inherent trends of the capitalism itself, what makes the cyclical changes of the capital happen as form that it finds to defend its profit rates. The raised empirical hypothesis which was pursued theoretically is that not have a radical change in the structure and the dominant logic of the world-wide economy, today is a continuity, in truth, a deepening of the imperialist age.